In haste with aloha : letters and diaries of Queen Emma, 1881-1885 - Emma, Queen, consort of Kamehameha IV, King of the Hawaiian Islands, 1836-1885 (University of Hawaiʻi Press, 2017)
This ambitious volume assembled by scholar David W. Forbes features a collection of ninety previously unpublished letters, as well as excerpts from two diaries, written between 1881 and 1885 by Hawaiian royal consort Queen Emma Kaleleonālani. In Haste with Aloha illuminates the last five years of the Queen's life and makes available an important record of royal social life and customs in nineteenth-century Hawai'i. Much of her earlier correspondence has been published in two books by the late Alfons L. Korn: The Victorian Visitors: An Account of the Hawaiian Kingdom, 1861-1866 and News from Molokai: Letters between Peter Kaeo and Queen Emma, 1873-1876. In her letters, almost all of which were written in English, Queen Emma provides a rare account of ali'i (royal) perspective, endowing modern readers and researchers with insight far beyond the limited available documentation of public speeches or printed statements. Besides the nuances of correspondence between the Queen and her recipients, there is much to be considered and analyzed in her descriptions of ali'i, many of them relatives to Emma, including Bernice Pauahi Bishop and Ruth Ke'elikōlani. With few comparable Hawaiian historical primary resource texts in print, In Haste with Aloha is a welcome addition, making accessible a preserved and treasured collection of documents drawn primarily from the Hawai'i State Archives, along with diaries in Bishop Museum Library and Archives. Fully transcribed and with annotation by Forbes, editor of the monumental four-volume Hawaiian National Bibliography and annotator of Hawaii's Story by Hawaii's Queen Liliuokalani, this text sheds light on the lives of Hawai'i's ruling class in the decade leading up to climactic political transition.